An ethnographic study of HIV/AIDS among Ayoreo sex workers: cultural factors and risk perception. Issue 23 (13th September 2013) - López‐Entrambasaguas, Olga M; Granero‐Molina, José; Fernández‐Sola, Cayetano
Abstract : Aims and objectives: To describe and understand Ayoreo sex workers' perceptions of HIV/AIDS and to identify factors that may affect the prevention of risk behaviours. Background: According to recent HIV/AIDS incidence reports, being female, indigenous and a sex worker means belonging to a maximum‐risk group, left in the background in terms of strategies for the fight against HIV. Although there has been research into intervention models in these populations, it is important to detail the perceptions of the problem from the perspective of sex workers from the affected ethnic groups. Design: This study used an ethnographic methodology that included participant observation and semi‐structured interviews. Methods: The research was conducted in two phases. First, participant observation was chosen to access and observe the behaviour of Ayoreo sex workers. The second phase was a semi‐structured interview with sex workers and key informants. The interviews, together with the field notes, were transcribed and analysed, following inductive strategies to find emerging themes. Results: Here, we present the results related to four emerging themes: the cultural acceptance of sex work as a useful economic activity; the lack of concern for sexually transmitted illnesses and the stigmatisation of people who are HIV seropositive; external factors that increase vulnerability such as difficulties in using a condom; and conflictive and unbalanced relationships between the Ayoreo people and the health system and health professionals. Conclusions: The health‐ and sexual reproduction‐related culture, the knowledge and attitudes of sex workers, external factors, and relationships with the health system and health professionals continue to place Ayoreo sex workers in high‐risk conditions in relation to sexually transmitted diseases and HIV/AIDS. Relevance to clinical practice: Employing cultural care as its base, nursing could develop programmes and interventions culturally adapted for the prevention of disease and the promotion of health in these populations.